APPLICATION OF LEMONGRASS AS NATURAL PRESERVATIVES FOR TOFU - Alwani Hamad; Eli Nurlaeli; Dea Y. Pradani; Asmiyenti D. Djalil; Dwi Hartanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Lemongrass (Cymbopogon citratus (DC.) Stapf, Poaceae) has been known for demonstrating anti-microbial activity against food spoilage bacteria. These antimicrobial properties can be further utilized for the development of natural food preservatives. In this study, the compounds present in water extract and essential oil of lemongrass were analyzed and their potential as tofu preservatives was evaluated. The water extract was prepared by the infusion method, while the essential oil was made by steam and water distillation. The phyto-chemicals composition of the water extract and essential oil was analyzed by qualitative colorimetric phyto-chemical screening and Gas Chromatography-Mass Spectroscopy (GC-MS) technique, respectively. Their preservative activity on tofu was evaluated by observing their ability to inhibit the growth of bacteria on the tofu and the physical changes of tofu during 10 days of preservation at room temperature. The results showed that lemongrass water extract contained terpenoids, tannins, and saponins. The GC-MS analysis identified 13 compounds in the essential oil. Neral, geranial, β-myrcene, juniper camphor, and viridiflorol were found as the major compounds. At concentration of 20%, lemongrass water extract demonstrated inhibition of bacterial growth during 10 day storage of tofu and improved the shelf life by 4 days longer from those of the negative control. In contrast, lemongrass essential oil did not show inhibitory activity in bacterial growth in tofu but it was capable of maintaining the color, odor, and texture of tofu as well as delaying the slime formation up to 4 days.